Accelerated atherosclerosis in haemodialysis patients; correlation of endothelial function with oxidative DNA damage - AŞICIOĞLU, EBRU (OXFORD UNIV PRESS, 2012)
Background. Accelerated atherosclerosis is the major cause of mortality in patients on chronic haemodialysis (HD). The aim of this study was to evaluate the relationship between oxidative DNA damage [8-hydroxy-2'-deoxyguanosine/deoxyguanosine ratio (8-OHdG/dG ratio)], oxidative stress biomarkers and endothelial function in HD patients as an indicator of atherosclerosis. Methods. Forty-four chronic HD patients without known atherosclerotic disease and 55 age- and sex-matched healthy individuals were included in the study. Plasma malondialdehyde (MDA) levels and 8-OHdG/dG ratio were determined as oxidative stress markers. Superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities were measured as antioxidants. Endothelial function was assessed by ultrasonography. Results. 8-OHdG/dG ratio and MDA levels were higher in HD patients than controls while SOD and GPx activities were lower in HD patients compared to controls. Flow-mediated dilatation FMD% in HD patients were lower than the control group (7.28 +/- 0.79 versus 11.18 +/- 0.82, P < 0.001). There was a significant negative correlation between FMD% and 8-OHdG/dG ratio (r = -0.678, P < 0.01) and MDA levels (r = 0.517, P < 0.01), while there was a significant positive correlation between FMD% and SOD (r = 0.538, P < 0.01) and GPx levels (r = 0.720, P < 0.01). Conclusions. Our data have demonstrated that HD patients exhibit increased oxidative DNA damage and decreased antioxidant activity. We propose that endothelial function is negatively correlated with 8-OHdG/dG ratio and positively correlated with antioxidant enzymes. To our knowledge, this is the first study to demonstrate the inverse relationship between endothelial function and plasma oxidative DNA damage in HD patients.
Keywords: endothelial dysfunction; haemodialysis; oxidative DNA damage; CARDIOVASCULAR RISK-FACTORS; CHRONIC-RENAL-FAILURE; PROTEIN PRODUCTS; OXIDANT STRESS; LEUKOCYTE DNA; MALONDIALDEHYDE; DYSFUNCTION; CAPACITY; CHILDREN; LIPIDS